Respuestas

2014-02-21T23:45:03+01:00

(3 elevado a la -4)elevado a la -1  3 elevado a la 4 =
(3^-4)^-1.3^4
= 3^4.3^4      (^-4)^-1 = ^(-4)(-1) = ^4    potencia de potencia
= 3^(4+4)      Prpoducto potencias de la misma base
= 3^8     RESULTADO FINAL

5elevado a la -9 . (25)elevado a 4 =
5^-9.(25)^4
= 5^-9.(5^2)^4
= 5^-9.5^8
= 5^(-9+8)
= 5^-1
= 1/5    RESULTADO FINAL

4 elevado a la 0.537
_                              =
4 elevado a la -0.463
(4^0.537)/(4^-0.463)
= 4^[0.537 - (-0.463)]
= 4^1
= 4  RESULTADO FINAL